2015
DOI: 10.1159/000441026
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Intrapulmonary Artery Doppler in Fetuses with Congenital Diaphragmatic Hernia

Abstract: Objective: To assess the learning curve for intrapulmonary artery Doppler in fetuses with congenital diaphragmatic hernia (CDH). Methods: Three fetal medicine fellows with the theoretic knowledge, but without prior experience, in the evaluation of intrapulmonary artery Doppler in CDH fetuses were selected. Each trainee and 1 experienced explorer assessed the intrapulmonary artery in the contralateral lung to the side of the hernia for calculation of 2 Doppler parameters - pulsatility index (PI) and peak early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…As a potential limitation of this study, it could be acknowledged that intrapulmonary Doppler insonation is technically difficult and it requires not only training to achieve competence but also very strict guidelines for acquisition and measurement. However, we recently demonstrated that even in inexperienced hands, intrapulmonary-artery Doppler in CDH yielded reliability after a substantial number of examinations 33 and it can be performed in virtually all cases with a low degree of disagreement between experienced examiners. 12,34 In conclusion, fetuses with CDH showed on average a constant lung dimension but with gradual increases in mean intrapulmonary-artery Doppler indices during the second half of pregnancy.…”
Section: Figurementioning
confidence: 99%
“…As a potential limitation of this study, it could be acknowledged that intrapulmonary Doppler insonation is technically difficult and it requires not only training to achieve competence but also very strict guidelines for acquisition and measurement. However, we recently demonstrated that even in inexperienced hands, intrapulmonary-artery Doppler in CDH yielded reliability after a substantial number of examinations 33 and it can be performed in virtually all cases with a low degree of disagreement between experienced examiners. 12,34 In conclusion, fetuses with CDH showed on average a constant lung dimension but with gradual increases in mean intrapulmonary-artery Doppler indices during the second half of pregnancy.…”
Section: Figurementioning
confidence: 99%
“…One potential explanation is the technical complexity of such measurements in the rabbit, due to smaller dimensions and marked displacement of the major pulmonary vessels, typical for CDH. 30 This might be partially responsible for the high variability of measurements within groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, any trained sonographer can perform fetal lung Doppler measurements, which are obtained in the same plane as that used for the measurement of o/e-LHR. In a previous study, CUSUM analysis demonstrated that the learning curve of IPA assessment comprises 53 measurements 30 . This is comparable with the learning curves for other commonly used fetal Doppler or ultrasound assessments, such as evaluation of the ductus venosus (80 examinations) and measurement of o/e-LHR (70 measurements) 31,32 .…”
Section: Principal Findingsmentioning
confidence: 93%